Study of Improving Fracture Toughness of Un-Saturated Polyester with Addition of Mixing Percentage of CPO Oils - Nusyirwan Adnand; Ilham S (METAL: Jurnal Sistem Mekanik dan Termal, 2022)
Unsaturated polyester is a polymer that is widely used as a basic matrix to form strong composites for engineering applications such as for cars, ships and aeroplanes. The advantages of using this material are owing to have a fairly high tensile strength when reinforced with appropriate reinforcing fibers, light and easy to shape. However, due to its brittle nature, this material cannot withstand shock loads. Therefore, it is necessary to overcome that weakness. Crude Palm Oil (CPO) can give benefits as a strengthening agent. However, its proper mixture to polyester need to be figured out so that it would help in improving crack resistance properties of this polyester. This can be done by determining of fracture resistance value of the mixture polymer. A crack resistance testing was carried out and crthe itical stress intensity factor was calculated based on ASTM D 5005. The composition of the CPO mixture was varied from 100%: 0%, 10%: 20%, 30%: 40%. From the test results, it can be identified that the greatest critical stress intensity factor is  = 15.787  MPa.m1/2. This is found out in composition of 30% CPO. Meanwhile the critical intensity factor of pure Unsaturated Polyester (UP) is only 2,023 MPa.m1/2. There is approximately 700% improvement that can be gained in mixing with CPO.